2008
DOI: 10.1007/s10658-008-9326-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential inhibitors against Sclerotinia sclerotiorum, produced by the fungus Myrothecium sp. associated with the marine sponge Axinella sp.

Abstract: Sclerotinia sclerotiorum is a worldwide ascomycete fungal plant pathogen, which causes enormous yield losses on major economic crops such as crucifers, grain legumes and several other plant families. The objective of this research was to isolate and characterise some bioactive products from cultures of fungi associated with the marine sponge Axinella sp. In total, nine fungal isolates were obtained from the marine sponge Axinella sp. collected from the South China Sea. A group of test strains, including two G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Trichothecenes (16)(17)(18)(19) have been recorded as important food mycotoxins that can cause serious harm to skin and mucosa [36]. Considering the high content of trichothecenes produced by this fungus, T. oligosporum should be seen as a potential mycotoxigenic fungus in food or feed.…”
Section: Resultsmentioning
confidence: 99%
“…Trichothecenes (16)(17)(18)(19) have been recorded as important food mycotoxins that can cause serious harm to skin and mucosa [36]. Considering the high content of trichothecenes produced by this fungus, T. oligosporum should be seen as a potential mycotoxigenic fungus in food or feed.…”
Section: Resultsmentioning
confidence: 99%
“…Since M. roridum produces two trichothecenes that significantly affect the rice blast pathogen (Wang et al 2007) and another Myrothecium sp. produces inhibitors that are effective against S. sclerotiorum (Xie et al 2008), it is at least possible that M. roridum will aid whitebark pine restoration at CLNP by acting against white pine blister rust. Further research is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…can produce biologically active trichothecenes that can potentially work against pathogens such as the rice blast fungus, Pyricularia oryzae Cavara (Wang et al 2007), and Sclerotinia sclerotiorum (Lib.) de Bary (Xie et al 2008). Myrothecium roridum has been described as plurivorous (Fitton and Holiday 1970), and although a total of 263 fungus-host records include 119 host genera, all reported hosts are Angiosperms (Farr et al 2009).…”
mentioning
confidence: 99%
“…This result is in accordance with a previous study which reported that crude ethyl acetate extract of Myrothecium sp. associated with the marine sponge, Axinella sp., was a potential producer of antifungal compounds against Sclerotinia sclerotiorum, a causal agent of stem rot in various crops 41 . Meanwhile, the crude extracts of three Emericella species including E. nidulans, E. rugulosa and E. variecolor showed high inhibition of the mycelial growth of eight of the tested plant pathogenic fungi at 1 g/L.…”
Section: Discussionmentioning
confidence: 99%